Pengaruh Tenure CEO terhadap Readability Narasi Pengungkapan - Ainun, Moh. Baqir (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2020)
This study examines the influence of CEO tenure on readability of narratives disclosure. This study also included company size and company age as control variables. The sample used in this study was 482 companies listed on the Indonesia Stock Exchange in 2018. There are not many studies on readability of narratives disclosure in Indonesia, so this study is expected to motivate academics to develop studies on disclosure narrative readability. The results showed that more longer CEO tenure could increase the readability of narratives disclosure. This condition can occur because CEO with longer tenure will be better able to communicate firm conditions in naratives disclosure that is simpler and easier to understand than CEO with shorter tenure. Moreover, firm size and firm age add complexity to narratives disclosure and decrease readability. This condition occurs because more larger the firm size and more older the firm age can create more items that must be disclosed in the narratives disclosure. This study can use to enrich the literature about influence of CEO tenure on readability of narratives disclosure.